About the geometrical stability of the marginal terms in variation series - Aksomaitis, Algimantas (Lietuvos matematikos rinkinys, 2004)
It was proved that the logistic minimum is geometrically min-stable, positional statistics  X(kN) ,  k > 1 are not geometrically stable, common minimum and maximum distributions are not asimptotically independent as the sample size is geometrical.
Keywords: extreme value; rate of convergence; max-geometric stability